Fcγ receptor IIB (FcγRIIB) maintains humoral tolerance in the human immune system in vivo. - Bärenwaldt, Anne; Lux, Anja; Danzer, Heike; Spriewald, Bernd M.; Ullrich, Evelyn; Heidkamp, Gordon Frederik; Dudziak, Diana; Nimmerjahn, Falk (Proceedings of the National Academy of Sciences of the United States of America, 2011)
Maintenance of immunological tolerance is crucial to prevent development of autoimmune disease. The production of autoantibodies is a hallmark of many autoimmune diseases and studies in mouse model systems suggest that inhibitory signaling molecules may be important checkpoints of humoral tolerance. By generating humanized mice with normal and functionally impaired Fcγ receptor IIB (FcγRIIB) variants, we show that the inhibitory Fcγ-receptor is a checkpoint of humoral tolerance in the human immune system in vivo. Impaired human FcγRIIB function resulted in the generation of higher levels of serum immunoglobulins, the production of different autoantibody specificities, and a higher proportion of human plasmablasts and plasma cells in vivo. Our results suggest that the inhibitory FcγRIIB may be an important checkpoint of humoral tolerance in the human immune system.